Hukum dan Keadilan Masyarakat (Analisis Sosiologi Hukum terhadap Kasus Hukum Masyarakat Miskin “Asyani” di Kabupaten Situbondo) - Umar Sholahudin (DIMENSI - Jurnal Sosiologi, 2016)
Law and justice community such as poles apart, not closer together. Law was born not just to create a social order (social order), but more than that, how law enforcement can provide a sense of justice for the community. One of thelegal cases that disturb public sense of justice is a legal case Asyani; theft of seven teak in Situbondo. This study aims to analyze the legal case Asyani, mainly related to how the perspective of sociology of law to explain the legal case Asyani grandmother ?; and sociological resolution mechanisms such as what it can provide a sense of legal justice for the poor as Asyani. The method used is descriptive-qualitative research approach to the sociology of law. The results showed; First, the case law Asyani grandmother should be resolved through legal mechanisms and approaches sociological and humanist. This settlement is known as the principle of restorative justice, the justice that is obtained outside the court positive law, through the recovery process in the spirit of mutual forgiveness between the perpetrator and the victim. Restorative justice is the best solution to resolve the legal problems that afflict the poor. Second, the working of the law more understandable and limited the application of the law is formal-procedural, without considering the sense of justice that is more substantive and sociological. Approach and application of the law legalistic-positivistic, only to bring justice which is legal-formal and procedural rigid, away from moral values and humanity. While the approach of sociology of law will be presenting more substantive justice that is based on the basis of ethical, moral and human values of society.